Disseminated fungal infection in an HIV-infected patient due to Aureobasidium pullulans. Issue 3 (18th July 2016) - van Hougenhouck-Tulleken, Wesley G.; Mathole, Garrison; Karstaedt, Alan; Govind, Nimmisha; Moodley, Magendhree; Seetharam, Sharona; Govender, Nelesh P.; Menezes, Colin N.
Abstract : In South Africa, novel fungal pathogens have emerged as an important cause of disease in HIV-infected individuals. The clinical presentation is characteristically prolonged, insidious and the diagnosis elusive, often being made post mortem. We report an HIV-infected individual with a systemic mycosis due to Aureobasidium pullulans, a ubiquitous dematiaceous mould which has not been described in HIV-infected individuals.